Optimising Hajj Service Management in the Office of the Ministry of Religious Affairs of Kotamobagu City - Mokodenseho, Sabil; Ibrahim, Yasin; Musa, Yahya; Mootalu , Sisman; Laudji, Ramlin Tamrin; Hanta, Samsudin; Daud, Sri; Kolu, Harun; Kaino , Elin (Westscience Press, 2024)
The optimization of Hajj service management stands as a pivotal endeavor for the Office of the Ministry of Religious Affairs in Kotamobagu City, North Sulawesi, as it seeks to facilitate a seamless pilgrimage experience for residents embarking on the sacred journey to Mecca. Through a qualitative analysis, this research explores the current practices, challenges, and opportunities for optimization in Hajj service management. In-depth interviews, focus group discussions, and document analysis were employed to gather insights from key informants and stakeholders directly involved in Hajj service management. The results reveal a nuanced understanding of the logistical complexities, communication gaps, and capacity-building needs inherent in managing Hajj services. Furthermore, opportunities for optimization, including leveraging technology, strengthening communication and coordination, and empowering stakeholders, are identified as promising avenues for enhancing the efficiency, effectiveness, and quality of Hajj services. By addressing these challenges and embracing innovative strategies, the Office of the Ministry of Religious Affairs can enhance the pilgrimage experience, uphold the sanctity of the Hajj journey, and serve the needs of pilgrims with diligence and compassion.